Enhanced Handover Algorithm for Quality of Service Maintenance in an Extended Service Set Wi-Fi Network - Derrick Qin Sheng, Wong (Derrick Wong Qin Sheng, 2025)
The technology of IEEE 802.11 has become one of the de facto networks utilized for indoor smart devices. During the connection, the wireless mobile node establishes a connection with Access Point (AP) to gain access to the network. With the increasing number of wireless devices, the frequencies used by the IEEE 802.11 network have become crowded, with many wireless devices available in the same location. A congested wireless network will not only cause wireless devices to have poor network data rates, but also lead to signal drops between the Access Point and the devices. To improve the reliability of IEEE 802.11 wireless network, the proposed enhanced roaming algorithm helps fulfil the requirements of the ongoing growth of new wireless devices. The enhanced roaming algorithm also helps balance loads among each BSS network without compromising the reliability of the wireless network. In this thesis, the study focuses on the performance of the enhanced roaming algorithm in Extended Service Set (ESS) network, which consists of multiple Basic Service Set (BSS) network. To validate the suggested approach, a simulation modelling was built using MATLAB to benchmark and analyse the results. For the enhanced roaming algorithm, two network parameters were considered: current associated stations and signal strength to the access point. These advancements underscore the potential for substantial improvements in Wi-Fi connectivity and reliability, fostering better user experiences and more robust network operations.